Comorbid TBI-depression costs in veterans: a chronic effect of neurotrauma consortium (CENC) study. (28th January 2019) - Dismuke-Greer, C. E.; Gebregziabher, M.; Byers, A. L.; Taber, D.; Axon, N.; Yaffe, K.; Egede, L. E.
ABSTRACT: Background : The U.S. Veterans Health Administration (VHA) provides depression treatment to veterans with Traumatic Brain Injury (TBI). VHA costs of comorbid TBI-depression were estimated by Operation Enduring Freedom/Operation Iraqi Freedom (OEF/OIF) status over 14 years. Methods : VHA-USING veterans with TBI DIAGNOSED IN 2000–2010 were followed through FY2014. TBI severity was determined using the Department of Defense criteria. Depression was identified by the Elixhauser algorithm. Generalized linear and seemingly unrelated regression models were used to estimate the impact of depression on annual per veteran and total VHA inpatient, outpatient, and pharmaceutical costs, by OEF/OIF status. Results : A total of 66.57% of pre-OEF/OIF and 87.46% of OEF/OIF veterans had depression. Depression was estimated to increase annual total ($1, 847), outpatient ($1, 558), and pharmaceutical ($287) costs for pre-OEF/OIF, and $1, 228, $1, 685, and $191 for OEF/OIF veterans. However, depression was estimated to lower annual inpatient costs by $648 per OEF/OIF veteran. The annual VHA cost for all veterans with comorbid TBI-depression was estimated at $1, 101, 329, 953. Conclusions : The estimated annual cost for Veterans with comorbid TBI-depression was more than $1 billion. TBI and depression screening/treatment may result in reduced inpatient VHA costs in OEF/OIF veterans exposed to TBI. VHA policymakers should consider screening for TBI and depression in pre-OEF/OIF veterans.